2018
DOI: 10.1002/pds.4389
|View full text |Cite
|
Sign up to set email alerts
|

New statin use and left ventricular structure: Estimating long‐term associations in the Multi‐Ethnic Study of Atherosclerosis (MESA)

Abstract: In contrast to previous small studies, we found very modest associations between statin use and indices of left ventricular remodeling over 10 years in this prospective study of a diverse cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Also in patients with non-ischaemic heart failure, atorvastatin treatment was associated with improvement in LV ejection fraction and LV chamber size [ 12 ], while another study in patients with hypertrophic cardiomyopathy demonstrated no effect of atorvastatin on reduction of LV mass [ 13 ]. Over 10 years of follow-up in 2389 participants free of established CVD from the Multi-Ethnic study of Atherosclerosis, a very modest association between statin use and less increase in LV mass assessed by cardiac magnetic resonance imaging was found [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also in patients with non-ischaemic heart failure, atorvastatin treatment was associated with improvement in LV ejection fraction and LV chamber size [ 12 ], while another study in patients with hypertrophic cardiomyopathy demonstrated no effect of atorvastatin on reduction of LV mass [ 13 ]. Over 10 years of follow-up in 2389 participants free of established CVD from the Multi-Ethnic study of Atherosclerosis, a very modest association between statin use and less increase in LV mass assessed by cardiac magnetic resonance imaging was found [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One MESA study examined the association between H2 receptor antagonists and changes in LV morphology [51], a relationship that had previously mostly only been studied in animal models. Another MESA study looked at new statin use and cardiac remodeling [52] and a UK Biobank study evaluated the impact of menopausal hormone therapy (MHT) in post-menopausal women free of CVD [53]. Compared to non-users, H2 receptor antagonist users had fewer detrimental changes in LV parameters.…”
Section: Associations With LV Structure and Functionmentioning
confidence: 99%